Syntax of Language in Visual Arts Education: Interactive Understanding through Image Prompt Generator - ronald, regina octavia (JOMANTARA, 2024)
The development of image generators in visual arts has garnered attention from the field of art education, and this article explores the interaction between language syntax and visual arts through the use of image prompt generators. Given the increasing utilization of AI technology in visual creativity within art education. The research methodology involves analyzing the language syntax within prompts used as instructions for image prompt generators, followed by a visual evaluation of the generated outcomes related to the language descriptions. Data analysis will highlight the correlation between language syntax instructions and visual interpretations, with the subjective of identifying the extent to which language usage influences visual artistic creativity. The results are expected to provide a deeper understanding of the impact of language syntax in creating visual artworks through image prompt generator technology. The implications of this research can enhance comprehension of language syntax usage in the context of visual arts and support the development of more interactive art education methods.